Language Clubs and Pedagogical Approach to Teach English: University of Parakou English Club case - Hounnou Azoua, Mathias (English Department FBS UNP, 2020)
This study aims at highlighting the English club as a tool for learners in need of English as a foreign language through which they practice and improve fluency. We use participative and consultative methods by means of questionnaire, interviews and Focus Group Discussion administration to stakeholders. Participants are four secondary schools, two private universities and one public University: 26 students, 10 administratives and 16 English teachers. The data was analyzed via descriptive statistics. Results indicated that most existing English clubs in the community contributed significantly to learners’ language fluency improvement and consequently to updating state of teachers and other actors. The more university of Parakou English Club members (UNIPAREC) participated to activities, the more they became fluent in English. The findings suggest pedagogical means to UNIPAREC for all categories of actors in the manipulation of the English language.